Single nucleotide polymorphisms and penicillin non-susceptibility among invasive Streptococcus pneumoniae from Vietnam and India: Insights from a comparative genomics study - Avani Panickar; Anand Manoharan; Sudha Ramaiah (Journal of Global Antimicrobial Resistance, 2025)
ABSTRACT: Objectives: Streptococcus pneumoniae (S. pneumoniae) is a significant cause of global morbidity and mortality across all age groups. Antimicrobial resistance (AMR), particularly penicillin resistance, is a significant treatment challenge. The study investigates AMR patterns among S. pneumoniae isolates from Vietnam, a country with high penicillin non-susceptibility, and India which in comparison has lower penicillin non-susceptibility. The present study focuses on penicillin resistance-associated genes and single nucleotide polymorphisms (SNPs), that contribute to pathogenicity. Methods: Invasive S. pneumoniae belonging to serotypes 23F (n = 13) and 19F (n = 20) genome sequences from Vietnam (n = 13) and India (n = 20) were retrieved and annotated to identify core genes. These genes were screened for antimicrobial resistance using the database. The genome sequences were mapped to a reference genome to detect the gene variants and were analysed for identifying specific mutations that contribute to pathogenicity. Results: Annotations identified pbp1a, pbp2b, and pbp2x (pbpX) as relevant AMR genes. In Vietnam, pbpX was a core gene, with 41 SNPs detected, of which 7 were deleterious mutations contributing to penicillin resistance. In contrast, pbpX was completely absent in the Indian genomes analysed. Conclusions: The current study highlights the genetic basis of penicillin non-susceptibility among invasive S. pneumoniae serotypes 23F and 19F and focuses on regional variations in resistance between India and Vietnam. The pbpX was identified as a core gene among penicillin-resistant pneumococci in Vietnam. In India, the absence of pbpX highlights genomic diversity, distinct from the uniformity observed in Vietnamese genomes. The study further predicts that deleterious SNPs are associated with pathogenicity.